Evaluating the effect of tanning response to sun exposure on the risk of skin diseases through Mendelian randomization - Ping, Weidong; Zhao, Qiming; Ge, Shuhong; Wang, Xin; Li, Fei; Huang, Xiaoxiang (Frontiers in Genetics, 2022)
Up till now, the relevance of tanning response to sun exposure and skin diseases has incomplete and inconsistent epidemiological observations. In this case, it is valuable to find out the causality of tanning response to sun exposure and skin diseases, and take a step further toward developing effective therapies as well as prevention methods. We investigated the causal effect of tanning response to sun exposure on ten major skin diseases which have been studied in recent large-scale genome-wide association studies (GWASs). Significant independent genetic variants from large-scale GWAS on ease of skin tanning (N = 453,065) are selected as the effective instrumental variables (IVs). For each skin disease, we extracted the summary statistics of those IVs (or their proxies) from the corresponding skin disease-GWAS as the valid IVs. Mendelian randomization (MR) was further performed to evaluate the causal association of ease of skin tanning with each of the skin diseases using different statistical methods including, inverse-variance weighted (IVW), the weighted median, MR-Egger. Sensitivity analysis was also conducted to evaluate the effect of horizontal pleiotropy and heterogeneity.